2010
DOI: 10.1143/jpsj.79.054702
|View full text |Cite
|
Sign up to set email alerts
|

One-by-One Introduction of Single Lattice Planes in a Bottlenecked Gold Contact during Stretching

Abstract: We observed the structural and conductance evolution of bottleneck-shaped gold contacts with [111] and [100] axes ([111] and [100] contacts) simultaneously during stretching. The [111] and [100] contacts were elastically stretched until a single (111) or (100) lattice plane was introduced by plastic deformation. The conductance decreased gradually by about 0.5 -0:8G 0 in the elastic regime, and subsequently stepped down at the plastic deformation. Since the conductance values changed depending on the strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
3
9
0
Order By: Relevance
“…During the thinning process, the Au contact became a bottlenecked shape which was suspended between two electrodes surrounded by three {111} and/or {100} facets as reported previously. 18 These observations are the same as mentioned by Strachan et al 8 ("unzipping model"). Also, we observed that both electrodes were asymmetric in shape at the failure, as shown by Heercshe et al 7 But, we found that very thin Au contacts fractured in a controlled manner even under electric bias, although they were reported to be broken spontaneously under no electric bias in the previous works.…”
supporting
confidence: 78%
“…During the thinning process, the Au contact became a bottlenecked shape which was suspended between two electrodes surrounded by three {111} and/or {100} facets as reported previously. 18 These observations are the same as mentioned by Strachan et al 8 ("unzipping model"). Also, we observed that both electrodes were asymmetric in shape at the failure, as shown by Heercshe et al 7 But, we found that very thin Au contacts fractured in a controlled manner even under electric bias, although they were reported to be broken spontaneously under no electric bias in the previous works.…”
supporting
confidence: 78%
“…Figure b,c presents the typical time evolution of the conductance and stiffness of a Pt nanocontact, respectively; while Figure d shows a series of TEM images acquired during stretching, which was controlled by the tube piezo at a rate of 0.08 nm/sec. The conductance showed distinct plateaus and stepwise changes over time, corresponding to the elastic and plastic deformation of the Pt nanocontact, respectively (Figure b) . Similarly, the stiffness exhibited stepwise change that was associated with the initiation of plastic deformation (Figure c).…”
Section: Resultssupporting
confidence: 88%
“…Gold SACs also have great potential in applied fields such as nanoelectronics. Many experimental [1][2][3][4][5][6][7][8][9][10] and theoretical [11][12][13][14][15][16][17][18][19][20][21][22][23][24] studies have been carried out to explain the SAC formation and its electrical characteristics. Using density-functional theory (DFT) simulations, it was found that during the nanowire elongation, the arrangement of the gold atoms changes from three-dimensional (3D) phases to a variety of two-dimensional (2D) phases and finally to SACs, which elongate gradually from one up to about nine atoms in the chain.…”
Section: Introductionmentioning
confidence: 99%